The mortality of patients with Parkinson's disease with deep brain stimulation - Kim, Ahro; Kim, Han-Joon; Kim, Aryun; Kim, Yoon; Kim, Ahwon; Ong, Jed Noel A.; Park, Hye Ran; Paek, Sun Ha; Jeon, Beomseok (Frontiers in Neurology, 2023)
Background and purpose: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is effective in improving motor function in patients with Parkinson’s disease (PD). This study aimed to investigate mortality associated with bilateral STN DBS in patients with PD, and to assess the factors associated with mortality and causes of death after DBS. Methods: We reviewed the medical records of 257 patients with PD who underwent bilateral STN DBS at the Movement Disorder Center at Seoul National University Hospital between March 2005 and November 2018. Patients were evaluated preoperatively, at 3, 6, and 12 months after surgery and annually thereafter. The cause and date of death were obtained from interviews with caregivers or from medical certificates at the last follow-up. Results: Of the 257 PD patients, 48 patients (18.7%) died, with a median time of death of 11.2 years after surgery. Pneumonia was the most common cause of death. Older age of disease onset, preoperative falling score while on medication, and higher preoperative total levodopa equivalent daily dose were associated with a higher risk of mortality. Conclusion: These results confirm the mortality outcome of STN DBS in patients with advanced PD.